Lectura de medios. De la audiencia ignorada al poder de las audiencias (2005)
In this article, presented as the final report of the research “Juvenile Audiences’ Education: a pedagogical proposal before media consumption habits,” there is a phenomenological analysis of social communication media consumptions such as: television, radio, press, and Internet. In this analysis, we call the attention about the need for educating audiences as a reply to the needs of juvenile population’s criterion formation, where despite the evidenced critical sense there has been established factors which participate in the full execution of freedom.